2012
DOI: 10.1523/jneurosci.0343-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Neurotransmitter Release at the Thalamocortical Synapse Instructs Barrel Formation But Not Axon Patterning in the Somatosensory Cortex

Abstract: To assess the impact of synaptic neurotransmitter release on neural circuit development, we analyzed barrel cortex formation after thalamic or cortical ablation of RIM1 and RIM2 proteins, which control synaptic vesicle fusion. Thalamus-specific deletion of RIMs reduced neurotransmission efficacy by 67%. A barrelless phenotype was found with a dissociation of effects on the presynaptic and postsynaptic cellular elements of the barrel. Presynaptically, thalamocortical axons formed a normal whisker map, whereas p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
75
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(86 citation statements)
references
References 73 publications
10
75
0
1
Order By: Relevance
“…Presynaptic Rab3-interacting molecules (RIMs) are active zone molecules involved in the control of neurotransmitter release (Kaeser et al, 2011; Wang et al, 1997). Previous work demonstrated that post-synaptic layer IV barrels do not form when neurotransmission is reduced selectively at thalamocortical synapses following presynaptic ablation of both RIM1 and RIM2 in double knockout (RIM DKO Sert ) mice (Narboux-Neme et al, 2012), as confirmed here (Figure 4A,B and S3A). At P14, a significant reduction of vascular density and branching was observed in barrel cortex layer IV of RIM DKO Sert mice compared to littermate controls (Figure 4C).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Presynaptic Rab3-interacting molecules (RIMs) are active zone molecules involved in the control of neurotransmitter release (Kaeser et al, 2011; Wang et al, 1997). Previous work demonstrated that post-synaptic layer IV barrels do not form when neurotransmission is reduced selectively at thalamocortical synapses following presynaptic ablation of both RIM1 and RIM2 in double knockout (RIM DKO Sert ) mice (Narboux-Neme et al, 2012), as confirmed here (Figure 4A,B and S3A). At P14, a significant reduction of vascular density and branching was observed in barrel cortex layer IV of RIM DKO Sert mice compared to littermate controls (Figure 4C).…”
Section: Resultssupporting
confidence: 85%
“…Moreover, there was no difference between RIM DKO Sert and WT mice in the distribution of three major capillary categories based upon different diameters (Figure 4C), suggesting a uniform impairment of vascular growth in these mutants. Similar genetic experiments demonstrated previously that removal of RIMs in TCAs resulted in normal presynaptic ultrastructure, but neurotransmitter release was strongly impaired in layer IV where we examined the vasculature (Narboux-Neme et al, 2012). Therefore, these data demonstrate that reduction of neurotransmitter release at thalamocortical synapses results in both postsynaptic neuronal disorganization and decrease of vascular density and branching in layer IV of the cerebral cortex.…”
Section: Resultssupporting
confidence: 75%
“…Quantification of the septal proportion of the barrel region based on CO staining showed no significant difference between Tsc1 ΔE12/ΔE12 (21%) and controls (25%, p=0.16, n=3 mice per genotype, two-sample two-tailed t-test; Figure 4L). To determine whether the organization of the cortical cell bodies was altered, we combined NeuN antibody labeling with CO staining to quantify cell density in the barrel hollows (outer limit of the CO+ barrel hollow is indicated by the dashed lines in Figure 4F,J) and the surrounding barrel wall region (indicated by the solid lines in Figure F,J) (Narboux-Neme et al, 2012). Mutants had lower neuron density in the barrel wall region (3.7 neurons/mm 2 ) than controls (Figure 4M; 4.5 neurons/mm 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Barrel formation is dependent on many synaptic proteins and activity-regulated molecules such as the receptor mGlur5, adenylate cyclase1, phospholipase C β1, synaptic Ras GTPase activating protein 1, and Rab3-interacting molecule 1 and 2 (47,48). Cortex-specific knockouts of particular transcription factors such as CCCTC-binding factor (CCTF), neurogenic differentiation 2 (NeuroD2), and DNA methyltransferase 1 (Dnmt1) (49-51) also display impaired or deficient barrel formation.…”
Section: Emx1crementioning
confidence: 99%